Management of Soft Tissue Upper Jaw Tumor in a 51 Year Old Female Patient at Sultan Fatah Hospital, Demak Regency: Case Report - Zam, Syarifah Nova Amiza; Reza, Faizal (Dentistry Faculty, 2024)
Background: Benign tumors are collections of cells, tissues or organs that grow slowly and usually enlarge with peripheral expansion, pushing on surrounding structures. Squamous odontogenic tumor (SOT) is a very rare benign epithelial intraosseous tumor, which can cause arising from the neoplastic transformation of Malassez epithelial cells on the lateral surface of the periodontal ligament. Objective : To discuss the management of odontogenic squamous tumors using conservative surgical excision. The goal of treatment for oral myxoma was surgical excision. Case management : A 51 year old female patient came to the SULTAN FATAH Hospital Polyclinic, Demak Regency on May 26 2023 with complaints of a lump on the upper left gum of the jaw. The patient felt the lump about 1 year ago. The patient does not feel pain in the lump. Clinical examination showed a lump in the upper jaw on the front of the patient's left side.Conclusion : Management of the patient undergoing surgical excision of the tumor with general anesthesia and infiltration in the case of odontogenic squamous tumor, based on subjective examination the patient complained of a lump with a tumor mass measuring 10 x 8 cm, redder than the surrounding tissue, round, not moving, attached to the gums of the upper jaw.